Distinct fungal successional trajectories following wildfire between soil horizons in a cold‐temperate forest. Issue 2 (14th April 2020) - Yang, Teng; Tedersoo, Leho; Lin, Xingwu; Fitzpatrick, Matthew C.; Jia, Yunsheng; Liu, Xu; Ni, Yingying; Shi, Yu; Lu, Pengpeng; Zhu, Jianguo; Chu, Haiyan
Summary: Soil fungi represent a major component of below‐ground biodiversity that determines the succession and recovery of forests after disturbance. However, their successional trajectories and driving mechanisms following wildfire remain unclear. We examined fungal biomass, richness, composition and enzymes across three soil horizons (Oe, A1 and A2) along a near‐complete fire chronosequence (1, 2, 8, 14, 30, 49 and  c.  260 yr) in cold‐temperate forests of the Great Khingan Mountains, China. The importance of soil properties, spatial distance and tree composition were also tested. Ectomycorrhizal fungal richness and β‐glucosidase activity were strongly reduced by burning and significantly increased with 'time since fire' in the Oe horizon but not in the mineral horizons. Time since fire and soil C : N ratio were the primary drivers of fungal composition in the Oe and A1/A2 horizons, respectively. Ectomycorrhizal fungal composition was remarkably sensitive to fire history in the Oe horizon, while saprotroph community was strongly affected by time since fire in the deeper soil horizon and this effect emerged 18 years after fire in the A2 horizon. Our study demonstrates pronounced horizon‐dependent successional trajectories following wildfire and indicates interactive effects of time since fire, soil stoichiometry and spatial distance in the reassembly of below‐ground fungal communities in a cold and fire‐prone region.